Brain structure alterations in depression: Psychoradiological evidence - Zhang, Fei‐Fei (CNS Neurosci Ther, 2018)
Depression is the leading cause of disability around the world, but little is known about its pathology. Currently, the diagnosis of depression is made based on clinical manifestations, with little objective evidence. Magnetic resonance imaging (MRI) has been used to investigate the pathological changes in brain anatomy associated with this disorder. MRI can identify structural alterations in depressive patients in vivo, which could make considerable contributions to clinical diagnosis and treatment. Numerous studies that focused on gray and white matter have found significant brain region alterations in major depressive disorder patients, such as in the frontal lobe, hippocampus, temporal lobe, thalamus, striatum, and amygdala. The results are inconsistent and controversial because of the different demographic and clinical characteristics. However, some regions overlapped; thus, we think that there may be a “hub” in MDD and that an impairment in these regions contributes to disease severity. Brain connections contain both structural connections and functional connections, which reflect disease from a different view and support that MDD may be caused by the interaction of multiple brain regions. According to previous reports, significant circuits include the frontal‐subcortical circuit, the suicide circuit, and the reward circuit. As has been recognized, the pathophysiology of major depressive disorder is complex and changeable. The current review focuses on the significant alterations in the gray and white matter of patients with the depressive disorder to generate a better understanding of the circuits. Moreover, identifying the nuances of depressive disorder and finding a biomarker will make a significant contribution to the guidance of clinical diagnosis and treatment.